IMPLEMENTASI RESTITUSI SEBAGAI UPAYA PEMULIHAN BAGI ANAK KORBAN KEKERASAN - Chaidar, Muhamad (Universitas Gorontalo, 2025)
Child protection is related to children who are facing criminal justice and children who are facing the law, both perpetrators and victims. In Indonesia, this is especially true in cases of sexual violence that most often occur in children. However, even though the rights of victims are fulfilled, regulations that protect victims are ineffective, so that the existence of victims is only passive, therefore the purpose of this study is to find out how to apply restitution as a restitutive effort for children victims of violence. This study uses normative legal research methods, focusing on the analysis of relevant laws and regulations and legal theories. Data were collected through literature research that included a variety of primary and secondary legal sources. The results of this study show that the understanding of both law enforcement and the public about the implementation of restitution and compensation is still low and there are many challenges. Restitution is compensation paid by the perpetrator based on a court decision, not always done due to the reluctance of the perpetrator and the lack of coercion mechanisms to enforce it. Efforts to improve the restitution mechanism must be carried out in order to provide justice and real recovery for the victims.